Expression and distribution of CD151 as a partner of alpha6 integrin in male germ cells - Jankovicova, J; Frolikova, M; Palenikova, V; Valášková, Eliška; Cerny, J; Secova, P; Bartokova, M; Horovska, L; Manaskova-Postlerova, P; Antalikova, J; Komrskova, K (Scientific reports, 2020)
The physiological importance of CD151 tetraspanin is known from somatic cells and its outside-in signalling through integrins was described. In male germ cells, two tetraspanins, CD9 and CD81, are involved in sperm-egg membrane fusion, and similarly to integrins, they occupy characteristic regions. We report here on a newly discovered presence of CD151 in sperm, and present its expression and distribution during spermatogenesis and sperm transition during the acrosome reaction. We traced CD151 gene and protein expression in testicular cell subpopulations, with strong enrichment in spermatogonia and spermatids. The testicular and epididymal localization pattern is designated to the sperm head primary fusion site called the equatorial segment and when compared to the acrosome vesicle status, CD151 was located into the inner acrosomal membrane overlying the nucleus. Moreover, we show CD151 interaction with α6 integrin subunit, which forms a dimer with β4 as a part of cis-protein interactions within sperm prior to gamete fusion. We used mammalian species with distinct sperm morphology and sperm maturation such as mouse and bull and compared the results with human. In conclusion, the delivered findings characterise CD151 as a novel sperm tetraspanin network member and provide knowledge on its physiology in male germ cells.
Keywords: Animals; Germ Cells; spermie; Testis; Spermatozoa; vazba proteinů; Structure-Activity Relationship; lidé; Protein Transport; Tetraspanin 24; fluorescenční protilátková technika; Mice; testis; Fluorescent Antibody Technique; myši; Integrin alpha6; transport proteinů; Models, Molecular; zárodečné buňky; Protein Conformation; molekulární modely; Male; konformace proteinů; exprese genu; vztahy mezi strukturou a aktivitou; zvířata; mužské pohlaví; integrin alfa6; antigeny CD151; Protein Binding; Gene Expression; Humans